Caracterização da fauna helmintológica de mamíferos atropelados nas rodovias BR-050 e BR-455 (Minas Gerais, Brasil) - Oliveira, Wilson Junior (2020)
Building of highways and roadkilling wildlife contribute to the reduction of animal population, which may generate local extinctions or worsen the situation of endangered species at national level. Nevertheless, carcasses of roadkill animals can be of great value for several studies, mainly parasite studies. Researchs on wildlife helminth diversity can help to understand the dynamics of their hosts, generating data that can assist conservationists in their preservation. The objective was to identify the helminths that parasitize Myrmecophaga tridactyla (giant anteater) and Tamandua tetradactyla (collared anteater) roadkilled on the BR-050 and BR-455 highways, Triangulo Mineiro, Minas Gerais state, Brazil, and to report the occurrence of Oncicola luehei in a roadkill Procyon cancrivorus (crab-eating raccoon). Four collared anteaters and three giant ones were necropsied, having their organs and gastrointestinal contents inspected for helminth collection. The recovered parasites were morphologically and morphometrically identified as: Graphidiops dissimilis (prevalence of 33.33%, found in the stomach of M. tridactyla); Physaloptera magnipapilla (prevalence of 66.6% and 50% in the small intestine of M. tridactyla and T. tetradactyla, respectively); Mathevotaenia spp. (prevalence of 25% and 66.6% in the small intestine of M. tridactyla and T. tetradactyla, respectively) and Gigantorhynchus echinodiscus (prevalence of 25% and 66.6% in the small intestine of M. tridactyla and T. tetradactyla, respectively). A new location was reported to Graphidiops dissimilis nematode, as well the exchange of helminths between the two anteater species, highlighting a possible interspecific relationship of these hosts. Necroscopic evaluation of Procyon cancrivorus was performed, recovering a single male helminth in its large intestine classified as Oncicola luehei. The main characteristics were the number and arrangement of hooks in proboscis, number and size of cement glands, as well the morphological and morphometric characteristics of testes and lemnisci. A new host and location was reported to the crab-eating raccoon specie.